How the garcia girls lost their accents eaudiobook - Alvarez, Julia (Recorded Books Inc., 2006)
Hailed by the Los Angeles Times as "simply wonderful" How the Garcia Girls Lost Their Accents captures the vivid lives of the Garcia sisters, four privileged and rebellious Dominican girls adapting to their new lives in America. In the 1960s, political tension forces the Garcia family away from Santo Domingo and toward the Bronx. The sisters all hit their strides in America, adapting and thriving despite cultural differences, language barriers, and prejudice. But Mami and Papi are more traditional, and they have far more difficulty adjusting to their new country. Making matters worse, the girls-frequently embarrassed by their parents-find ways to rebel against them. A touching coming-of-age tale, this enthralling book perfectly illuminates the intergenerational struggles and multicultural clashes so common to the American immigrant family.